Transmigration of Neutrophils From Patients With Familial Mediterranean Fever Causes Increased Cell Activation - Martirosyan, Anush; Poghosyan, David; Ghonyan, Susanna; Mkrtchyan, Nune; Amaryan, Gayane; Manukyan, Gayane (Frontiers in Immunology, 2021)
Familial Mediterranean fever (FMF) is caused by pyrin-encoding MEFV gene mutations and characterized by the self-limiting periods of intense inflammation, which are mainly mediated by a massive influx of polymorphonuclear neutrophils (PMNs) into the inflamed sites. Perturbation of actin polymerization by different pathogens was shown to activate the pyrin inflammasome. Our aim was to test whether cytoskeletal dynamics in the absence of pathogens may cause abnormal activation of PMNs from FMF patients. We also aimed to characterize immunophenotypes of circulating neutrophils and their functional activity. Circulating PMNs displayed heterogeneity in terms of cell size, granularity and immunophenotypes. Particularly, PMNs from the patients in acute flares (FMF-A) exhibited a characteristic of aged/activated cells (small cell size and granularity, up-regulated CXCR4), while PMNs form the patients in remission period (FMF-R) displayed mixed fresh/aged cell characteristics (normal cell size and granularity, up-regulated CD11b, CD49d, CXCR4, and CD62L). The findings may suggest that sterile tissue-infiltrated PMNs undergo reverse migration back to bone marrow and may explain why these PMNs do not cause immune-mediated tissue damage. A multidirectional expression of FcγRs on neutrophils during acute flares was also noteworthy: up-regulation of FcγRI and down-regulation of FcγRII/FcγRIII. We also observed spontaneous and fMPL-induced activation of PMNs from the patients after transmigration through inserts as seen by the increased expression of CD11b and intracellular expression of IL-1β. Our study suggests heightened sensitivity of mutated pyrin inflammasome towards cytoskeletal modifications in the absence of pathogens.